Knowledge Translation Outcomes Following Innovative Continuing Education. Issue 4 (2015) - Schreiber, Joe; Perry, Susan; Downey, Patricia; Williamson, Ann
Abstract : Introduction. : Physical therapists (PTs) and other health care providers often struggle with integrating new knowledge into clinical practice. Some preliminary evidence suggests that continuing education courses (CECs) are more likely to lead to clinical behavior change if activities explicitly aimed at supporting knowledge translation (KT) are included. This study describes an innovative CEC, including specific KT activities, and then describes the experiences of the attendees relative to applying the knowledge shared during the CEC. Subjects. : Seventeen PTs attended the CEC and participated in this project. These individuals worked in adult settings and participated as clinical instructors for the physical therapy program. Methods. : Over 3 separate 4‐hour sessions, attendees listened to traditional lectures on gait speed, interventions to improve skill acquisition, and database searching. They also participated in smallgroup discussions related to CEC content. Online and homework activities were also included. Participants were interviewed at a 6‐month follow‐up session. The interviews were transcribed and analyzed using an interpretive description framework. Quantitative self‐report data on changes in knowledge and behavior, achievement of goals related to course content, and course satisfaction data were also gathered. Results. : Analysis led to the emergence of several themes. These included positive reactions to the structure and format of the course, success with clinical implementation and with influencing colleagues' use of course content related to gait speed and skill acquisition, limited success with increasing frequency activities such as seeking out and obtaining scientific research evidence from peerreviewed journals, and persistent barriers that limited application of course content. Discussion and Conclusions. : Attendees expressed a preference for the multicomponent format and reported some success with implementing course content. Physical therapy CECs should include elements that support clinical practice change.